PEDAGOGICAL CONDITIONS FOR THE FORMATION OF HUMANITIES TEACHERS’ PROFESSIONAL REFLECTION IN POSTGRADUATE EDUCATIO - Сєнчина, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
Transformations that take place in modern education are intended to promote professional and personal growth of a teacher. The latter is impossible without the teacher having the advanced pedagogical reflection, which allows to implement a systemic, holistic regulation of pedagogical activity, and, therefore, to solve problems related to the mastery of innovative, creative instruments. The purpose of the article is to define and substantiate the pedagogical conditions for the formation of professional reflection of humanities teachers in postgraduate education. Analysis of scientific literature on the problem under study, observation of educational activities, content analysis of scientific and methodological provision of educational programs of institutes of postgraduate pedagogical education allowed us to determine and substantiate a number of pedagogical conditions that as a result of their introduction into the system of postgraduate education provide formation of pedagogical reflection of humanities teachers. Determination of the orientation of the system of postgraduate pedagogical education to the targeted updating of reflexivity and the formation of pedagogical reflection of humanities teachers as a factor in their personal and professional development was defined as the first pedagogical condition. The second pedagogical condition was identified as the organization of the reflexive educational environment, which contributes to the cultivation of reflection and the development of reflexive abilities. The third pedagogical condition was determined by the updating of the content of postgraduate pedagogical education and the implementation of reflexive and active-based technologies. As a result of the implementation of this condition, activation of the professional and research activities of teachers on the correction of personal and professional "Self-Image", self-development of reflexive abilities and reflexive culture is achieved. The fourth condition for the effective formation of the pedagogical reflection of humanities teachers in postgraduate education was determined as a dominant role of the reflexive practice.